16p11.2 Deletion Syndrome Mice Display Sensory and Ultrasonic Vocalization Deficits During Social Interactions. Issue 5 (7th February 2015) - Yang, Mu; Mahrt, Elena J.; Lewis, Freeman; Foley, Gillian; Portmann, Thomas; Dolmetsch, Ricardo E.; Portfors, Christine V.; Crawley, Jacqueline N.
<x xml:space="preserve">Abstract</x> Recurrent deletions and duplications at chromosomal region 16p11.2 are variably associated with speech delay, autism spectrum disorder, developmental delay, schizophrenia, and cognitive impairments. Social communication deficits are a primary diagnostic symptom of autism. Here we investigated ultrasonic vocalizations (USVs) in young adult male 16p11.2 deletion mice during a novel three‐phase male–female social interaction test that detects vocalizations emitted by a male in the presence of an estrous female, how the male changes its calling when the female is suddenly absent, and the extent to which calls resume when the female returns. Strikingly fewer vocalizations were detected in two independent cohorts of 16p11.2 heterozygous deletion males (+/−) during the first exposure to an unfamiliar estrous female, as compared to wildtype littermates (+/+). When the female was removed, +/+ emitted calls, but at a much lower level, whereas +/− males called minimally. Sensory and motor abnormalities were detected in +/−, including higher nociceptive thresholds, a complete absence of acoustic startle responses, and hearing loss in all +/− as confirmed by lack of auditory brainstem responses to frequencies between 8 and 100 kHz. Stereotyped circling and backflipping appeared in a small percentage of individuals, as previously reported. However, these sensory and motor phenotypes could not directly explain the low vocalizations in 16p11.2 deletion mice, since (a) +/− males displayed normal abilities to emit vocalizations when the female was subsequently reintroduced, and (b) +/− vocalized less than +/+ to social odor cues delivered on an inanimate cotton swab. Our findings support the concept that mouse USVs in social settings represent a response to social cues, and that 16p11.2 deletion mice are deficient in their initial USVs responses to novel social cues. Autism Res2015, 8: 507–521. © 2015 International Society for Autism Research, Wiley Periodicals, Inc.